Hospital level under-utilization of minimally invasive surgery in the United States: retrospective review. (8th July 2014) - Cooper, Michol A; Hutfless, Susan; Segev, Dorry L; Ibrahim, Andrew; Lyu, Heather; Makary, Martin A
Abstract : Objective To determine casemix adjusted hospital level utilization of minimally invasive surgery for four common surgical procedures (appendectomy, colectomy, total abdominal hysterectomy, and lung lobectomy) in the United States. Design Retrospective review. Setting United States. Participants Nationwide inpatient sample database, United States 2010. Methods For each procedure, a propensity score model was used to calculate the predicted proportion of minimally invasive operations for each hospital based on patient characteristics. For each procedure, hospitals were categorized into thirds (low, medium, and high) based on their actual to predicted proportion of utilization of minimally invasive surgery. Main outcome measures The primary outcome measures were the actual and predicted proportion of procedures performed with minimally invasive surgery. Secondary outcome measures included surgical complications and hospital characteristics. Results Mean hospital utilization of minimally invasive surgery was 71.0% (423/596) for appendectomy (range 40.9-93.1% (244-555)), 28.4% (154/541) for colectomy (6.7-49.8% (36/541-269/541)), 13.0% (65/499) for hysterectomy (0.0-33.6% (0/499-168/499)), and 32.0% (67/208) for lung lobectomy (3.6-65.7% (7.5/208-137/208)). Utilization of minimally invasive surgery was highly variable for each procedure type. There was noticeable discordance between actual and predicted utilization of the surgery (range of actual to predicted ratio for appendectomy 0-1.49; colectomy 0-3.88; hysterectomy 0-6.68; lung lobectomy 0-2.51). Surgical complications were less common with minimally invasive surgery compared with open surgery, respectively: overall rate for appendectomy 3.94% (1439/36 513) v 7.90% (958/12 123), P<0.001; for colectomy: 13.8% (1689/12 242) v 35.8% (8837/24 687), P<0.001; for hysterectomy: 4.69% (270/5757) v 6.64% (1988/29 940), P<0.001; and for lung lobectomy: 17.1% (367/2145) v 25.4% (971/3824), P<0.05. High utilization of minimally invasive surgery was associated with urban location (appendectomy: odds ratio 4.66, 95% confidence interval 1.17 to 18.5; colectomy: 4.59, 1.04 to 20.3; hysterectomy: 15.0, 2.98 to 75.0), large hospital size (hysterectomy: 8.70, 1.62 to 46.8), teaching hospital (hysterectomy: 5.41, 1.27 to 23.1), Midwest region (appendectomy: 7.85, 1.26 to 49.1), south region (appendectomy: 21.0, 3.79 to 117; colectomy: 10.0, 1.83 to 54.7), and west region (appendectomy: 9.33, 1.48 to 58.8). Conclusion Hospital utilization of minimally invasive surgery for appendectomy, colectomy, total abdominal hysterectomy, and lung lobectomy varies widely in the United States, representing a disparity in the surgical care delivered nationwide.